Islamic Social Finance as Source of Financing Agricultural Sector in Indonesia - Nurfalah, Irfan; Al-Parisi , Salman (Ekonomi Islam Indonesia, 2023)
The shrinking of rice fields causes crop yields to decrease. Apart from that, financing in this sector is not attractive to investors because it is high risk. The minimal financing of agricultural sector credit is the reason for the author to discuss the problems faced in agricultural sector credit. The source of agricultural credit capital is the synergy between agricultural zakat and the government budget for food security and is allocated according to needs. So, sharia banking, the government and Baznas collaborate in raising funds for agricultural credit. This paper takes an example of an agricultural sector financing scheme from Japan which has been successfully implemented. However, Japan's credit financing comes from government funds only. This encourages the author to innovate credit financing in the agricultural sector, especially food diversification commodities, namely the synergy between agricultural zakat and the government budget for food security. Agricultural zakat is centralized by Baznas and then handed over to the Indonesian Agricultural Association (API). API determines the budget allocation of these funds and then submits it to Bank Indonesia (BI). BI hands it back to sharia banking to be credited to farmers with a predetermined allocation and the remaining allocated funds are deposited.